Divulgação científica em rede: o website como ferramenta instrucional para o ensino de ciências - Tenório, Kleitson José Lima (2021)
The internet plays a fundamental role in contemporary computerized communication, since, besides allowing the sharing of information, it cooperates to the collaborative construction of academic research and dissemination of scientific knowledge. Integrating and using technological resources through the web and the internet is essential to dynamize the relations of society with science. In face of this assumption, the objective of this work was to describe how the websites can enhance the scientific dissemination, for this, we identified how digital tools can contribute to the Science Dissemination, based on studies that contributed to the scientific knowledge dissemination and we listed the benefits of websites for scientific democratization. This study was designed from the qualitative approach type conducted in three stages, from pre-analysis, the exploration of the material and the treatment of the obtained data. The results showed that it is possible to develop the dissemination of science using the websites, allied to the technological resources described in this research, showed techniques on how you can use digital resources to expand the dialogue with the public. We built a website that hosted a course of scientific dissemination through Google Sites, monitored by Google Analytics where it was possible to see parameters, previously invisible to the eyes of the researcher as for example audience metrics, location of access and type of device used, such statistical data in graphical form helped us to understand the interaction of course participants with the site and showed important points for improving the resource so that it benefits the dissemination of science on the web. Key-words: Science Popularization. Science Teaching. Google Sites Translated with www.DeepL.com/Translator (free version)